Overexpression, crystallization and preliminary X‐ray crystallographic analysis of glucuronoxylan xylanohydrolase (Xyn30A) from Clostridium thermocellum. Issue 12 (1st December 2013) - Verma, Anil Kumar; Goyal, Arun; Freire, Filipe; Bule, Pedro; Venditto, Immacolata; Brás, Joana L. A.; Santos, Helena; Cardoso, Vânia; Bonifácio, Cecília; Thompson, Andrew; Romão, Maria João; Prates, José A. M.; et al.
<x xml:space="preserve">Abstract</x> The modular carbohydrate‐active enzyme belonging to glycoside hydrolase family 30 (GH30) from Clostridium thermocellum (CtXynGH30) is a cellulosomal protein which plays an important role in plant cell‐wall degradation. The full‐length CtXynGH30 contains an N‐terminal catalytic module (Xyn30A) followed by a family 6 carbohydrate‐binding module (CBM6) and a dockerin at the C‐terminus. The recombinant protein has a molecular mass of 45 kDa. Preliminary structural characterization was carried out on Xyn30A crystallized in different conditions. All tested crystals belonged to space group P1 with one molecule in the asymmetric unit. Molecular replacement has been used to solve the Xyn30A structure.